CONSTRUCTION AND VALIDATION OF EDUCATIONAL TECHNOLOGY FOR HIV/AIDS PREVENTION IN WOMEN DEPRIVED OF FREEDOM - Alana Vanessa Sousa Santos Borges; Marcos André de Matos; José Henrique Barbosa de Souza; Ketllen Raiara Ferreira Santos Freire; Fabiana Ribeiro de Sousa; Victor de Jesus Florentino (Universidade Federal do Paraná, 2023)
Objective: to describe the process of elaboration and validation of educational technology for prevention of Human Immunodeficiency Virus in female population deprived of freedom. Method: methodological study conducted in a prison complex in the Midwest of Brazil, from January to July 2019, using a four-point Likert scale. Data were analyzed with Cronbach's Alpha and KAPPA tests. A minimum Content Validity Index of 0.80 was considered for validation and minimum 75% agreement. Results: The items of the material were relevant with a total Content Validity Index of (CVI t=0.87) for specialists and (CVI t=0.95) for women. The specialists evaluated the booklet, classifying it with a "superior" degree of recommendation (average of 91%). There were adjustments, reaching, in the end, a concordance index higher than 88.7%. Conclusion: we believe that this technology represents an advance for Public Health, since it used reliable and appropriate measures and instruments for the target audience.